Läsningens disciplinering: Om litteratursyn och litteraturundervisning - Bergenmar, Jenny (Tidskrift för litteraturvetenskap, 2010)
The Teaching of Literature and the Disciplining of Reading The article discusses how the institutional norm of critical reading tends to rule out other ways of reading. Instead of mapping different kinds of reading practices and providing useful concepts for describing them, the teaching of literature often tends to be prescriptive and aimed at reproducing this specific way of reading, and in extension, a certain view of literature related to it. This problem is discussed in connection to Rita Felski’s »modes of textual engagements,« Michael Warner’s questioning of what qualifies as a critical reading, and Eve Kosofsky Sedgwick’s concept of »reparative reading.«